Comparative analysis of hemoglobin S and normal populations based on β-Globin Like Gene Cluster Haplotype Variation in Denizli, Turkey; Historical-Geographical perspectives and mutation age estimation ) - Ozturk, Onur; Arikan, Sanem; Atalay, Ayfer; Omer Atalay, Erol (Annals of Medical Research, 2021)
None